Best Practices in Training and Preparedness for Medical Emergencies: From Dental School to Private Practice - Alini Agnes; Jesse W. Manton (Taylor & Francis Group, 2024)
Background Medical urgencies and emergencies require immediate attention and competent management by dentists and their teams. Having a proper emergency medical kit to support management of these situations is essential.Types of Studies Reviewed A review of the available literature was performed, including peer-reviewed articles, American Dental Association (ADA) Commission on Dental Accreditation standards, ADA website articles, and publications from professional societies.Results An emergency medical kit is a key component of a well-designed medical emergency response system in a dental practice. Initial and regular training sessions to optimize dentist and team member knowledge, skills, and experiences are essential to maintaining emergency preparedness. A description of modern predoctoral emergency medical training is provided.Practical Implications Dental schools and practices should carefully assess their emergency medical kits, training, and protocols to ensure a system is in place to initiate evaluation and management of acutely unwell patients.